Hysteresis Effects in Economics – Different Methods for Describing Economic Path-dependence - Ansgar Belke; Matthias Göcke; Laura Werner (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2014)
Relations between economic variables are often characterized by a situation where initial conditions and the past realizations of economic variables matter. I.e. past (transient) exogenous disturbances and past states of the economic system do have an influence on the current economic relations. Typical examples are the dynamics of (un)employment in business cycles and the dynamics of the nexus of exchange rate and exports. Since the standard characteristics of hysteresis apply - i.e. permanent effects of a temporary stimulus, resulting in path-dependent multiple equilibria - these economic phenomena are correctly titled as 'hysteresis'. Empirical research in economics is using different methods in order to capture path-dependent effects. First econometric approaches tried to describe these effects by simple timeseries processes with unit- (or zero)-root dynamics. However, since unit-root-dynamics are not related to genuine multiple equilibria but on the order of integration of the time series, these first attempts were expanded by more sophisticated time-series models integrating structural breaks, threshold-cointegration or non-linear autoregressive distributed lag-models. Another branch of empirical studies tries to keep closer to the original concept of the macroloop, trying to apply an explicit Mayergoyz/ Preisach aggregation procedure for heterogeneous firms - if microeconomic information is available based on panel-data - or by using simple algorithms analogous to mechanical-play in order to apply simple OLS-regression methods on a filtered/transformed input-output relation. In this paper, we give an overview of the implementation of hysteresis in economics, with an emphasis on two aspects: (1) the differentiation between micro- and macroeconomic hysteresis including an outline of an adequate aggregation procedure, and (2) different methods applied in econometrics in order to capture economic path-dependency empirically. – – Der Zusammenhang zwischen ökonomischen Größen kennzeichnet sich oftmals dadurch, dass die Ausgangssituation und vergangene Werte von Bedeutung sind. Vergangene (temporäre) exogene Störungen und Zustände des Systems haben einen Einfluss auf die gegenwärtigen Zusammenhänge. Typische Beispiele hierfür sind die Entwicklung der Arbeitslosigkeit im Laufe des Konjunkturzyklus' oder der Zusammenhang zwischen Wechselkursen und Exporten. Diese Phänomene lassen sich somit als Hysterese klassifizieren - also die permanente Auswirkung eines temporären Effektes mit dem Ergebnis eines pfadabhängigen Gleichgewichtes. Empirische Untersuchungen in den Wirtschaftswissenschaften verwenden verschiedene Methoden, um diese Phänomene abzubilden. Einerseits wird versucht diese Effekte über stationäre bzw. nicht-stationäre Prozesse mittels Einheitswurzeltests abzubilden. Hierbei wird aber nur auf den Integrationsgrad der Zeitreihen eingegangen, so dass multiple Gleichgewichte nicht untersucht werden können. Insofern wurden diese Ansätze bald durch Verfahren ersetzt, die Strukturbrüche, Kointegration oder nicht lineare Zusammenhänge erlauben. Ein anderer Zweig der empirischen Forschung konzentriert sich stärker auf das ursprüngliche Konzept einer makroökonomischen Hystereseschleife. Hierbei wird explizit eine Mayergoyz/Preisach-Aggregation für heterogenen Firmen vorgenommen. Dieser Beitrag liefert eine Übersicht über das Hysteresephänomen in ökonomischen Zusammenhängen, wobei besonders auf zwei Aspekte eingegangen wird. Erstens wird sorgfältig zwischen Hysterese auf mikro- und makroökonomischer Ebene unterschieden und zweitens werden die verschieden ökonometrischen Methoden dargestellt, um Pfadabhängigkeit abbilden zu können.
Keywords: C51; C62; 330; play-hysteresis; modelling techniques; switching/spline regression; path-dependence